SEASONAL CHANGES IN THE TEMPERATURE, SALINITY AND PLANKTON VOLUME AT PORT BLAIR, ANDAMANS - Rengarajan, K; Marichamy, R (Indian Journal of Fisheries, 2011)
The seasonal changes in the temperature, salinity and plankton volume at Port Blair, Andamans, during the period 1964 to 1970 have been investigated and the changes correlated with the meteorological conditions of the locality. The atmospheric temperature exhibited a clear double oscillation in a year, the maxima occurring in April and November. The range of fluctuation was generally less than 10Â°C. The surface temperature closely followed the atmospheric temperature and exhibited a clear double oscillation. The surface temperature was invariably lower than the atmospheric temperature. The temperature of the surface water steadily increased from January to April registering a sharp fall in May due to the onset of the south-west monsoon. The surface salinity increased steadily from January to April registering a fall in May which coincided with the onset of the monsoon. Higher values were restored during the post-monsoon period. The surface water was fairly rich in plankton during the colder months. An inverse relationship was noticed between the abundance of plankton and temperature/salinity.